INCREASING WORD COMPREHENSION BY USING CROSSWORD PUZZLE GAME AT THE EIGHT GRADES OF SMPN 273 JAKARTA - Retno Rahayuningsih; Ary Iswanto Wibowo; Delish Meta Tiana (Lingua, 2022)
Word comprehension is the essential learning for students to learn English well and correctly, because it is the way to improve the students’ English vocabulary mastery to can practice the students’ ability in understand the reading text English well and correctly. The problem the writer had outlined in this research deals largely with the study of reading. The subject of this research was twenty-eight students at the eighth grades of SMPN 273 Jakarta. The design of the research was classroom action research. It was conducted in two cycles; in cycle I was done with two meeting and cycle II was done with two meetings. In this research the students were given pre-test before treatment and post-test after treatment. The research aimed to find out whether the used crossword puzzle game technique could increase word comprehension the students in English mastery. The data collection technique in this research was observation, field note, test, and documentation. The purposes of given pre-test and post-test are to know how far the students’ word comprehend in English before and after being given treatment. The criteria of students’ who got score at least 70. The class could be said successful in achieving the material if 85% of the students in that class got score at least 70 and they had activation at class more than 50%. The average of pre-test score in cycle I was 65 or 10 students got pass score, and post-test 1 70.7 or 16 students got good score and the average post-test 2 in cycle II was 77.8 or 24 students got good score. This fact showed that teaching English by using crossword puzzle game technique can increase word comprehension in reading English